The Language Attitude of Senior High School Students Towards English Language - Fia Vauliany Br Siringo-ringo; Ketut Artawa; Yana Qomariana (Jurnal Langua, 2023)
English is one of the most important languages for students to learn since it is the most spoken language in the world and has long become the global lingua franca. Hence, this study is aiming to find out the attitude of students, particularly senior high school students towards English language. This study applied the combination the two methods, quantitative one in analyzing the data, and qualitative method in providing the results of the research. Meaning, the data observed were in the form of circular diagrams, and the provided results were in the form of words collection. The data were obtained from a prepared questionnaire concerning student’s language attitude towards English language. The subjects of the questionnaire were the students of X-5 and X-7 graders of SMA Negeri 1 Kabanjahe for the academic year of 2022 with a total number of fifty students. The result showed that the dominant attitude reflected by the students is positive attitude. Keywords: language attitude, English language, senior high school